Histidine-Proline-Rich Glycoprotein Binding to Platelets Mediated by Transition Metals - Horne, McDonald K., III; Merryman, Paula K.; Cullinane, Ann M. (Thrombosis and Haemostasis, 2001)
Histidine-proline-rich glycoprotein (HPRG) binds zinc, which in turn promotes HPRG binding to lymphocytes and monocytes. We examined the possibility that zinc and other transition metals also promote HPRG binding to platelets. Only non-specific, unsaturable association of HPRG with resting or activated platelets was observed in the absence of transition metals. However, nickel, cobalt, copper, cadmium, and zinc greatly increased HPRG association with the cells. In the presence of zinc, specific, saturable binding of HPRG to platelets was demonstrated. The cell binding capacity for HPRG could be increased by increasing the zinc saturation of HPRG from 10% to 30% as well as by activating the platelets with thrombin. Because platelets contain relatively high concentrations of secretable zinc, it is possible that significant amounts of HPRG bind to activated platelets at sites of blood clotting and that this has a physiologic function.
Keywords: Histidine-proline-rich glycoprotein; platelets; fibrinolysis; zinc